A novel de novo IL2RG nonsense mutation in a pediatric patient with X-linked severe combined immunodeficiency - Wang, Lin; Ren, Aiyan; He, Yuanyuan; Wang, Lu; Wang, Sixi; Xie, Xin; Tan, Mei; Chen, Yan; Huang, Pei; Du, Zuochen (Frontiers in Genetics, 2025)
ObjectiveThe study aims to describe the clinical manifestations, immunophenotype, and gene mutation characteristics of a child with X-linked severe combined immunodeficiency (X-SCID) caused by an IL2RG mutation (NM_000206.3; exon 2 c.216C > A, p.Cys72*), and to contextualize these findings through a review of reported cases of X-SCID associated with Talaromyces marneffei (T. marneffei) infection, highlighting the immunological and diagnostic relevance of the mutation.MethodsThe clinical data of a child with X-SCID caused by an IL2RG mutation were retrospectively analyzed. Whole-exome sequencing and Sanger sequencing were used to identify the mutation, and flow cytometry was employed for immunophenotypic analysis to assess the impact of the mutation on immune function. A literature review was performed on reported cases of X-SCID associated with T. marneffei infection identified in PubMed and Scopus.ResultsThe patient was a 4-month-old male infant presenting with chronic diarrhea, recurrent fever, and anemia, with poor response to antibiotic treatment. Laboratory tests indicated T. marneffei infection, significantly reduced T lymphocytes and NK cells, and decreased levels of immunoglobulins (IgG, IgA, IgE). Genetic testing revealed a de novo hemizygous mutation in the IL2RG gene (NM_000206.3; exon2 c.216C > A, p.Cys72*), which has not been previously reported. Flow cytometric analysis showed a severe reduction in T lymphocytes, absence of CD8 + T cells, reduced NK cells, and a normal number of B lymphocytes. Six cases of IL2RG gene mutation combined with T. marneffei infection were identified in the literature, most showing fever, hepatosplenomegaly and respiratory tract infection.ConclusionThis case of X-SCID caused by a novel de novo IL2RG mutation expands the known mutation spectrum and highlights its immunological and diagnostic relevance. The review of reported cases of X-SCID with T. marneffei infection further clarifies genotype–phenotype correlations and supports improved recognition of such rare presentations.